2013
DOI: 10.1186/scrt163
|View full text |Cite
|
Sign up to set email alerts
|

BAY11 enhances OCT4 synthetic mRNA expression in adult human skin cells

Abstract: IntroductionThe OCT4 transcription factor is involved in many cellular processes, including development, reprogramming, maintaining pluripotency and differentiation. Synthetic OCT4 mRNA was recently used (in conjunction with other reprogramming factors) to generate human induced pluripotent stem cells. Here, we discovered that BAY 11-7082 (BAY11), at least partially through an NF-κB-inhibition based mechanism, could significantly increase the expression of OCT4 following transfection of synthetic mRNA (synRNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…However, it was also reported that small molecule inhibitors of type-I interferon signaling showed no enhancing effects on the overall production of proteins in single transfection of IVT-mRNA. 12) On the other hand, Awe et al reported that inhibitors of nuclear factor-kappaB (NF-κB) signaling, BAY11-708 and BX795, significantly elevated the transfection efficiency of the IVT-mRNA. 13) Other possible targets are the proteins that are involved in integrated stress responses (ISRs), since cellular stresses including the recognition of exogenous RNA induce the suppression of canonical cap-dependent translation via the phosphorylation eIF2α .…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also reported that small molecule inhibitors of type-I interferon signaling showed no enhancing effects on the overall production of proteins in single transfection of IVT-mRNA. 12) On the other hand, Awe et al reported that inhibitors of nuclear factor-kappaB (NF-κB) signaling, BAY11-708 and BX795, significantly elevated the transfection efficiency of the IVT-mRNA. 13) Other possible targets are the proteins that are involved in integrated stress responses (ISRs), since cellular stresses including the recognition of exogenous RNA induce the suppression of canonical cap-dependent translation via the phosphorylation eIF2α .…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we hypothesize that active inhibition of PAMPs and/or the IFN activation pathway is also a reasonable strategy to enhance mRNA transfection. Indeed, this concept of active inhibition was recently reviewed [ 9 ] and a proof-of-principle study focused on the use of small molecules Bay11 and BX795 were reported [ 12 ]. Interestingly, many other small molecules that had been reported to inhibit IFN were also available commercially.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Awe et al (2013) reported enhanced in vitro translation of the transcription factor OCT4 from a synthetic mRNA upon BAY11 supplementation [35]. However, the enhanced OCT4 translation was not achieved when the type I IFN decoy receptor B18R was supplemented, indicating that the observed increase in translation was independent of type I interferons [35].…”
Section: Discussionmentioning
confidence: 96%